Muhammadiyah Boarding School (MBS) sebagai Alternatif Model Pesantren (Potret Pendidikan Islam di Era Kontemporer) - Ibnu Habibi (Proceedings of Annual Conference for Muslim Scholars, 2017)
This paper intends to review the role of Muhammadiyah Boarding School (MBS) as an alternative model of schools in the contemporary era. Pesantren is the oldest Islamic education system in Indonesia. It provides very great contribution to the nation of Indonesia, both in education and in the fight against the invaders. In education schools participate in the intellectual life of the nation. However the performance of schools is still considered less qualified and urgently need to be developed in the future. Communities in the present era (contemporary) increasingly make schools as an alternative educational institution. At the time of science and technology is developing rapidly, at a time when modern philosophy of human life moral and religious crisis, and at the time of global free trade closer to the gate, where boarding appear increasingly in need of people. This shows the role, importance and significance of the existence of pesantren in the contemporary era.Keywords: Muhammadiyah Boarding School, Pesantren